LAPORAN KASUS: SELULITIS PRESEPTAL DENGAN ABSES FRONTAL (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2022)
The objective of study is to report a case and management of preseptal cellulitis caused by dental infection. A case report, a 45 years old man presented at outpatient clinic with painful and swollen eyelids on the both eyes in 3 days, fever, and headache. The bumps in both eyes burst by themselves 1 day before hospital admission. The complaint begins with a toothache, then swelling in the cheek, then the swelling spreads to the eyes and head. Computed Tomograph (CT) scan examination revealed Soft tissue swelling in the right frontotemporoparietal region, left frontotemporoparietooccipital to periorbital bilateral and right maxilla with massive air density and air fluid level on the left frontotemproparietooccipital according to the picture of Abscess. The patient consulted to neurosurgeon doctor and perform an abscess drainage incision. Adequate treatment and multidisciplinary management are needed to prevent more severe complications. .